2008
DOI: 10.1111/j.1533-2500.2008.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐validation of the Children's and Infants' Postoperative Pain Scale in Brazilian Children

Abstract: Based on the results obtained, we can infer that CHIPPS is a valid and reliable tool for Brazilian children aged 0 to 5 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
12
0
5
Order By: Relevance
“…Despite a limited training with reference to time, the three raters showed a fairly high agreement regarding both pain assessment tools’ items (range CHIPPS: 0.918–0.981, CHIPPS‐ADJ: 0.900–0.986, NFCS‐R: 0.910–0.980). Interrater reliabilities for the NFCS‐R were comparable to those established in the literature (Grunau et al, ), interrater reliabilities for the CHIPPS/CHIPPS‐ADJ were higher than those reported in the literature (0.89–0.93; Alves et al, ; Buettner & Finke, ; Suraseranivongse et al, ), presumably due to the large amount of time that had been spent in advance to clarify coding criteria for the CHIPPS(‐ADJ) items because of the unavailability of a manual.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Despite a limited training with reference to time, the three raters showed a fairly high agreement regarding both pain assessment tools’ items (range CHIPPS: 0.918–0.981, CHIPPS‐ADJ: 0.900–0.986, NFCS‐R: 0.910–0.980). Interrater reliabilities for the NFCS‐R were comparable to those established in the literature (Grunau et al, ), interrater reliabilities for the CHIPPS/CHIPPS‐ADJ were higher than those reported in the literature (0.89–0.93; Alves et al, ; Buettner & Finke, ; Suraseranivongse et al, ), presumably due to the large amount of time that had been spent in advance to clarify coding criteria for the CHIPPS(‐ADJ) items because of the unavailability of a manual.…”
Section: Discussionsupporting
confidence: 67%
“…Good reliability indices were established. Cronbach’s alpha ranged from 0.92 to 0.96 (Buettner & Finke, ), interrater reliabilites from 0.89 to 0.93 (Alves et al, ; Buettner & Finke, ; Suraseranivongse et al, ). With regard to validity, correlation with the Toddler‐Preschooler Postoperative Pain Scale (von Baeyer & Spagrud, ) was 0.45 and the administration of potent analgesics in infants led to a reduction in the CHIPPS values (Buettner & Finke, ).…”
Section: Methodsmentioning
confidence: 99%
“…CHIPPS, RIPS and NAPI associated the three following behavioral indicators: facial expression, crying and motor activity, as well as others, such as response to touch in NAPI, consolability and response to touch 1725 - 27 …”
Section: Resultsmentioning
confidence: 99%
“…A CHIPPS, a RIPS e a NAPI associaram os três indicadores comportamentais: expressão facial, choro e atividade motora, além de outras, como resposta ao toque na NAPI, consolabilidade e resposta ao toque 1725 - 27 …”
Section: Resultsunclassified
“…The sum of each item determines the total score, which can result in values ranging from 0 to 10 points. In CHIPPS, the higher the score, the greater the intensity of pain (8) . Data collection took place over a period of 4 months and was performed by two observers: observer A was one of the authors of the study, while observer B was a nurse or nursing technician responsible for neonate care during that shift.…”
Section: Methodsmentioning
confidence: 99%